Direct vat set modifier capable of adjusting crosslinking degree as well as preparation method and application of direct vat set modifier

By grafting functional components such as decrosslinking agents into the direct-injection modifier to adjust the cross-linking degree and adhesion of asphalt, the problems of unstable performance and low construction efficiency of traditional modifiers are solved, and efficient Asphalt pavement construction and durability.

CN119350633APending Publication Date: 2025-01-24ZHONGLU JIAOKE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411493906.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

When traditional direct-injection modifiers are matched with asphalt from different origins and processes, there are differences in crosslinking, network density and morphology, resulting in unstable performance, low construction efficiency, poor adhesion, and prone to particle loss and looseness. etc.

Method used

By grafting a decrosslinking agent, a polar coupling agent, a catalytic crosslinking agent and a tackifier onto the main chain segment of the thermoplastic elastomer, a direct-throw modifier can be formed that can adjust the degree of crosslinking. During the high-temperature mixing process, this modifier de-crosslinks the agent to form a complex and reduces the cross-linking degree of asphalt; during the transportation and paving process, the tackifier and thermoplastic elastomer molecules migrate to the aggregate surface to improve adhesion. properties; under the action of rolling force, the catalytic cross-linking agent promotes the formation of cross-linked network and improves the viscosity and toughness.

Benefits of technology

It realizes the adjustment of the cross-linking degree of different types of asphalt, improves the adhesion and viscosity of the asphalt mixture, and ensures the durability and construction efficiency of the asphalt pavement structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005100782240000031
    Figure BDA0005100782240000031
  • Figure BDA0005100782240000032
    Figure BDA0005100782240000032
  • Figure BDA0005100782240000081
    Figure BDA0005100782240000081
Patent Text Reader

Abstract

The invention relates to the technical field of pavement materials, in particular to a direct vat set modifier capable of adjusting the crosslinking degree as well as a preparation method and application of the direct vat set modifier. The main chain segment of the thermoplastic elastomer is grafted with a polymer of a decrosslinking agent, a polar coupling agent, a catalytic crosslinking promoting agent and a tackifier from outside to inside; the direct vat set modifier is prepared from the following components in parts by weight: 30 to 40 parts of a thermoplastic elastomer, 10 to 20 parts of a decrosslinking agent, 5 to 10 parts of a polar coupling agent, 10 to 20 parts of a catalytic crosslinking promoting agent and 10 to 20 parts of a tackifier, wherein in the heating and mixing process of the direct vat set modifier and the asphalt, the grafting of the main chain segment is gradually released from outside to inside. Through dissociation of the decrosslinking agent grafted on the polar coupling agent, a complex can be formed to act on decrosslinking of asphalt, so that the crosslinking degree is reduced, and the durability of an asphalt pavement structure is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of pavement materials, and in particular relates to a direct-injection modifier with adjustable cross-linking degree, a preparation method and application thereof. Background Art

[0002] Direct-injection modifiers can be used as an effective substitute for wet-process modified asphalt at this stage. They can quickly melt and disperse during the mixing process to achieve the purpose of modifying asphalt, overcoming the problems of poor long-term storage stability and easy aging under heat of traditional wet-process modified asphalt. They are easy to use and have adjustable dosage. Currently, the widely used direct-injection modifiers include: direct-injection RP modifiers for improving high-temperature rutting resistance, anti-rutting agents, high modulus agents, and TPS, HVA and ZTS high-viscosity modifiers for drainage pavement.

[0003] Traditional direct-injection modifiers are made by mixing high-molecular polymers, additives and other materials, melting them and then extruding them into a mold. After direct injection, they undergo melting and free swelling to achieve asphalt modification and aggregate coating. Compared with the wet modification process, due to the lack of strong shear, the cross-linking network density and morphology are greatly different from the wet method. In actual applications, direct-injection modifiers are compatible with base asphalt or modified asphalt of different origins and processes, and the cross-linking degree, network density and morphology of different asphalts are also different. The same cross-linking degree can be ensured by adjusting the ratio of asphalt and modifier, but the modified asphalt still has a variety of cross-linking network densities and morphologies, and the performance differences are obvious. Due to the compatibility selectivity for different types of asphalt and the differences in wet modification, the promotion and use of traditional direct-injection modifiers are limited.

[0004] When direct-injection modifiers are used in combination with modified asphalt, the modified asphalt itself has a high degree of cross-linking, a high network density, and a high system viscosity. The reintroduction of polymer molecules into the modifier will cause a sharp increase in the viscosity of the system, making the mixing and paving process extremely difficult and reducing construction efficiency. The presence of high cross-linking degree and high network density also hinders the effective migration of the viscosity enhancer in the modifier, making it impossible to form an effective bond with the aggregate, resulting in poor adhesion, leading to frequent defects such as particle loss and looseness during later use. Summary of the invention

[0005] The purpose of the present invention is to provide a direct-injection modifier with adjustable cross-linking degree, and a preparation method and an application method thereof. The cross-linking agent grafted on the polar coupling agent dissociates to form a complex, which acts on the asphalt to de-crosslink and reduce the cross-linking degree. During the mixing and transportation of the mixture, the viscosity enhancer and thermoplastic elastomer molecules migrate to the aggregate surface to improve adhesion. During the paving process, under the action of rolling pressure, the catalytic cross-linking agent acts on the thermoplastic elastomer molecular chain segments to form a cross-linked network, thereby improving viscosity and toughness and ensuring the durability of the asphalt pavement structure.

[0006] The above technical objectives of the present invention are achieved through the following technical solutions:

[0007] The first aspect of the present invention is to provide a direct-injection modifier with adjustable crosslinking degree, wherein the direct-injection modifier is based on a thermoplastic elastomer, and a polymer of a crosslinking agent, a polar coupling agent, a catalytic crosslinking agent and a tackifier is grafted from outside to inside on the main chain segment of the thermoplastic elastomer;

[0008] Calculated by weight, the components for preparing the direct injection modifier include:

[0009] 30-40 parts of thermoplastic elastomer, 10-20 parts of crosslinking agent, 5-10 parts of polar coupling agent, 10-20 parts of catalytic crosslinking agent and 10-20 parts of tackifier;

[0010] In the process of heating and mixing the direct injection modifier and asphalt, the grafting of the main chain segment is released step by step from the outside to the inside.

[0011] Furthermore, after the release of the cross-linking agent, a complex centered on the zinc ion can be formed.

[0012] Further, the cross-linking agent includes thiazole and zinc disulfide carbamate;

[0013] Among them, the structural formula of thiazole is as follows:

[0014]

[0015] Wherein, n is 1 or 2, and R is one of hydrogen, zinc or a benzo group.

[0016] Further, the structural formula of zinc disulfide carbamate is as follows:

[0017]

[0018] Wherein, R1 is any one of methyl, ethyl, butyl, phenyl or benyl;

[0019] R2 is any one of methyl, ethyl, butyl, phenyl or benzyl.

[0020] Furthermore, one end of the polar coupling agent is a polar group, connecting the catalytic cross-linking agent and the tackifier;

[0021] The other end is a hydrolyzable functional group, which connects to the cross-linking agent by charge action.

[0022] Furthermore, the molecular structure of the catalytic cross-linking agent contains R-CHO, wherein R is an alkyl group.

[0023] Furthermore, the tackifier contains one or more of -NH3, -COOH or -CONH.

[0024] Further, the thermoplastic elastomer is one or a combination of linear SBS and star-shaped SBS;

[0025] The relative molecular mass range is 80000~120000;

[0026] The block ratio is 8:2 to 6:4;

[0027] The relative density is 0.92~0.95.

[0028] The second aspect of the present invention is to provide a method for preparing a direct-injection modifier with adjustable crosslinking degree, comprising the following steps:

[0029] Grafting a catalytic crosslinking agent and a tackifier onto the main chain segment of the thermoplastic elastomer to obtain a precursor 1;

[0030] Grafting a polar coupling agent onto precursor 1 to obtain precursor 2;

[0031] Grafting a cross-linking agent onto the hydrolyzable functional group of the polar coupling agent of the precursor 2 to obtain an intermediate;

[0032] The intermediate is extruded to obtain a direct injection modifier.

[0033] The third aspect of the present invention is to provide an application of a direct-injection modifier capable of adjusting the degree of crosslinking, comprising the following steps:

[0034] Mixing the direct-injection modifier with the heated aggregate;

[0035] Adding asphalt and mixing to obtain asphalt mixture;

[0036] Spread and roll the asphalt mixture.

[0037] Furthermore, the application method of the direct injection modifier comprises the following steps:

[0038] Direct mixing of modifier: Add graded aggregates according to the mix ratio requirements, heat to 160-190℃, mix, and add modifiers to the heated aggregates according to the specified proportion;

[0039] After mixing for 15 to 60 seconds, add the proportion of heated asphalt, and mix the direct-injection modifier with asphalt and aggregate in the mixing plant for 40 to 60 seconds after it melts.

[0040] The mixed asphalt mixture is transported insulated and, after arriving on site, is discharged and spread evenly, slowly, and continuously. After initial compaction, repeated compaction, and final compaction, it is cooled to room temperature.

[0041] In summary, the present invention has the following beneficial effects:

[0042] (1) The present invention provides a technology for step-by-step grafting of functional components in a direct-injection modifier, and by matching the use process of the modifier, the cross-linking degree of different types of asphalt can be adjusted. After the modifier is directly injected, under the action of the high-temperature mixing process, the cross-linking agent grafted on the polar coupling agent dissociates to form a complex, which acts on the asphalt to de-crosslink and reduce the cross-linking degree; during the mixing and transportation of the mixture, the tackifier and thermoplastic elastomer molecules migrate to the aggregate surface to improve adhesion; during the paving process, under the action of rolling pressure, the catalytic cross-linking agent acts on the thermoplastic elastomer molecular chain segments to form a cross-linked network, which improves viscosity and toughness and ensures the durability of the asphalt pavement structure.

[0043] (2) The present invention uses a crosslinking agent to adjust the degree of crosslinking. The crosslinking agent is composed of thiazoles and disulfide carbamates, which can dissociate from the polar coupling agent at high temperature and react to form a complex centered on zinc ions. At room temperature and pressure, the carbon-carbon double bonds on the main chain of the thermoplastic elastomer are rearranged by inducing and polarizing the coordination bonds, resulting in the rearrangement of the sulfur-sulfur bonds, forming a crosslinking state in which the main chain of the macromolecule is intact and the sulfur-sulfur bonds are broken. The low degree of crosslinking in the mixing of asphalt and modified asphalt is ensured, so that the asphalt remains in a high-temperature and low-viscosity state, which is conducive to construction.

[0044] (3) The present invention utilizes aldehyde-catalyzed crosslinking agents and thickeners to promote the crosslinking of asphalt and modifier molecules after the de-crosslinking step is completed. Aldehyde-catalyzed crosslinking agents can form an adsorption effect with the active components in the asphalt, replace H in the asphalt and undergo a condensation reaction, thereby increasing the molecular weight of the asphalt and presenting a continuous streamline distribution, thereby enhancing the degree of crosslinking; the amphiphilic phase groups in the thickener can connect the asphalt and thermoplastic elastomer molecules to form a crosslinking network. The two ensure that the modified asphalt is highly crosslinked and improves adhesion.

[0045] (4) The present invention utilizes a grafted tackifier containing polar functional groups to improve the adhesion between aggregate and asphalt. It can be connected to the aggregate surface through hydrogen bonds and van der Waals forces of -NH3, -COOH, and -CONH polar groups; at the same time, the -COOH contained in the tackifier reacts chemically with the alkaline groups on the surface of the polar aggregate to form a chemical bond; the surfactant in the tackifier reacts with the surface of the aggregate through charge-oriented adsorption, providing a strong connection between the asphalt and the aggregate, further improving the adhesion between the asphalt and the aggregate, and ensuring the durability of the asphalt pavement structure. DETAILED DESCRIPTION

[0046] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, a direct-injection modifier with adjustable crosslinking degree and its preparation method and application method proposed in the present invention, its specific implementation method, characteristics and effects are described in detail as follows.

[0047] Sources of raw materials used in the specific implementation method:

[0048] Cross-linking agent: 2-mercaptobenzothiazole, CAS: 149-30-4; zinc dimethyldithiocarbamate, CAS: 37-30-4.

[0049] Thermoplastic elastomer: SBS, 1301, linear structure, block ratio of 30 / 70; SBS, Daogai No. 2, star structure, block ratio of 40 / 60.

[0050] Polar coupling agent: KH550, CAS: 919-30-2; KH570, CAS: 2530-85-0;

[0051] Catalytic cross-linking agent: glutaraldehyde, CAS: 111-30-8; trioxymethylene, CAS: 68002-20-0; formaldehyde, CAS: 50-00-0.

[0052] Tackifier: rosin resin, CAS: 8050-09-7, molecular formula C 19 H 29 COOH; terpene resin, molecular formula: C 10 H 16 , CAS No.: 138-86-3; petroleum resin, CAS: 68131-77-1; phenolic resin, CAS: 9003-35-4, molecular formula C7H8O2.

[0053] Asphalt, Shuanglong 70# asphalt, ID asphalt and PG76-22 asphalt produced by Yangzi Petrochemical Company, the technical indicators are shown in Table 1:

[0054] Table 1 Asphalt technical parameters

[0055] Test Project 70# Asphalt ID Asphalt PG76 Asphalt <![CDATA[Penetration (25°C) / (10 -1 mm)]]> 70 53.1 55 Softening point / ℃ 46.7 81 87 Elongation (5℃) / cm / 34.4 36 Number average molecular weight Mw 170501 276305 Weight average molecular weight Mn 0 148305 223329

[0056] Note: Mw and Mn represent the degree of crosslinking. The larger the value, the greater the degree of crosslinking.

[0057] This specific embodiment first provides a direct-injection modifier with adjustable crosslinking degree, wherein the direct-injection modifier is a thermoplastic elastomer matrix, and a polymer of a crosslinking agent, a polar coupling agent, a catalytic crosslinking agent and a tackifier is grafted from the outside to the inside on the main chain segment of the thermoplastic elastomer;

[0058] Calculated by weight, the components of the direct injection modifier include:

[0059] 30-40 parts of thermoplastic elastomer, 10-20 parts of crosslinking agent, 5-10 parts of polar coupling agent, 10-20 parts of catalytic crosslinking agent and 10-20 parts of tackifier;

[0060] Among them, during the heated mixing process of the direct-injection modifier and asphalt, the grafting of the main chain segment of the thermoplastic elastomer is released step by step from the outside to the inside.

[0061] It can be understood that in this specific embodiment, the components grafted from outside to inside on the main chain segment of the direct-injection modifier are released step by step during the process of direct-injection modifier from direct injection to mixing and paving, corresponding to the de-crosslinking process in the mixing process and the catalytic crosslinking after paving and the adhesion process with the aggregate. The specific process is as follows:

[0062] First, after the direct injection modifier is directly injected, under the action of high temperature, the outermost grafted cross-linking agent on the thermoplastic elastomer is released under the action of high temperature to form a cross-linked state.

[0063] Secondly, when the de-crosslinking agent is released, the polar coupling agent dissociates during the mixing and transportation process, and the catalytic crosslinking agent and thickener grafted on the main chain segment are released. When a high crosslinking state is not formed, the SBS in the thickener and thermoplastic elastomer migrates to the aggregate surface to form adhesion.

[0064] Finally, under the action of rolling pressure during the paving process, the aldehyde cross-linking promoter and the amphiphilic phase resin in the tackifier can enhance the degree of cross-linking and improve adhesion.

[0065] It is understandable that the above process can adjust the cross-linking degree of different types of asphalt by matching the use of modifiers. After the modifier is directly added, under the action of high-temperature mixing process, the cross-linking agent grafted on the polar coupling agent dissociates to form a complex, which acts on the asphalt to de-crosslink and reduce the cross-linking degree; during the mixing and transportation of the mixture, the tackifier and thermoplastic elastomer molecules migrate to the aggregate surface to improve adhesion; during the paving process, under the action of rolling pressure, the catalytic cross-linking agent acts on the thermoplastic elastomer molecular chain segments to form a cross-linking network, improves viscosity and toughness, and ensures the durability of the asphalt pavement structure.

[0066] In some preferred embodiments, the cross-linking agent can form a complex centered on zinc ions after being released.

[0067] In some preferred embodiments, the cross-linking agent includes thiazole and zinc disulfide carbamate, and the structural formula of thiazole is as follows:

[0068]

[0069] Wherein, n is 1 or 2, and R is one of hydrogen, zinc or a benzo group.

[0070] In some preferred embodiments, the structural formula of zinc disulfide carbamate is as follows:

[0071]

[0072] Wherein, R1 is any one of methyl, ethyl, butyl, phenyl or benyl;

[0073] R2 is any one of methyl, ethyl, butyl, phenyl or benzyl.

[0074] It is understandable that the cross-linking agent used in this embodiment, after being released by high-temperature mixing, thiazole and zinc disulfide carbamate can undergo a complex reaction to form a complex centered on Zn ions, as follows:

[0075] The complex can de-crosslink modified asphalts that are cross-linked by sulfurization, such as SBS modified asphalt, PG asphalt, ID asphalt, IC asphalt and other modified asphalts. Under the action of the coordination bonds of the complex, the carbon-carbon double bonds on the main chain of the asphalt macromolecules are induced to polarize, and the electrons in the carbon-carbon double bonds are transferred, causing the sulfur cross-linking bonds to rearrange, thereby causing the sulfur cross-linking bonds to break. The carbon-carbon double bonds will also rearrange to form a main chain broken structure to ensure the basic properties of the asphalt, but the sulfur cross-linking agent will break, reducing the degree of cross-linking in the asphalt and modified asphalt, allowing the asphalt to remain in a high temperature and low viscosity state, which is conducive to construction.

[0076] In some preferred embodiments, in the cross-linking agent, the mass ratio of thiazole to zinc disulfide carbamate is 1:1.

[0077] In some preferred embodiments, the molecular weight of thiazole is 160-400, and the molecular weight of zinc disulfide carbamate is 100-500.

[0078] In some preferred embodiments, one end of the polar coupling agent is a polar group, connecting the catalytic cross-linking agent and the tackifier; the other end is a hydrolyzable functional group, connecting the cross-linking agent by charge action.

[0079] In some more preferred embodiments, the chemical structure of the polar coupling agent is as follows:

[0080] Y(CH2) n SiX3; wherein Y is one of alkyl, phenyl, vinyl, epoxy, amino, and mercapto, X is one of chloro, methoxy, and ethoxy, and n is an integer of 0 to 3.

[0081] It can be understood that in this specific embodiment, the selection of the polar coupling agent can make the direct-cast modifier, under high-temperature mixing, the charge force of the Y group is slightly stronger than the intermolecular force of the X group, and the functional components can be released in an orderly manner; specifically, in the polar coupling agent provided by this specific embodiment, Y is a polar group, which can be connected with the -CHO group of the catalytic cross-linking agent and the -NH3, -COOH, and -CONH polar groups of the tackifier through the charge action, and X is a hydrolyzable functional group, which is weakly connected with the R group in the de-crosslinking agent through the intermolecular force; the two ends of the group isolate the de-crosslinking agent from the cross-linking agent through different bonding effects, and the high temperature acts on the weak connection of the intermolecular force, which can preferentially release the de-crosslinking agent; the mixing and transportation process (high temperature and stirring exist at the same time) acts on the charge action between the polar groups to release the cross-linking agent.

[0082] In some preferred embodiments, the molecular structure of the catalytic cross-linking agent contains R-CHO, wherein R is an alkyl group.

[0083] In some more preferred implementations, the catalytic cross-linking agent is composed of one or more of formaldehyde, trioxymethylene and glutaraldehyde.

[0084] It can be understood that R-CHO can form an adsorption effect with the active components in asphalt, and a condensation reaction occurs after replacing H, which makes the modified asphalt particles larger and presents a continuous streamline distribution, thereby enhancing the degree of cross-linking.

[0085] In some preferred embodiments, the tackifier contains one or more of -NH3, -COOH or -CONH.

[0086] In some more preferred embodiments, the tackifier is one or more combinations of rosin resin, terpene resin, petroleum resin, and phenolic resin.

[0087] In some preferred embodiments, the thermoplastic elastomer is one or a combination of linear SBS and star-shaped SBS;

[0088] The relative molecular mass range is 80000~120000;

[0089] The block ratio is 8:2 to 6:4;

[0090] The relative density is 0.92~0.95.

[0091] It is understandable that the thermoplastic elastomer under the above-defined conditions can provide a more stable main chain, which is convenient for the assembly, grafting and release of functional components.

[0092] This specific embodiment also provides a method for preparing a direct-injection modifier with adjustable crosslinking degree, comprising the following steps:

[0093] Grafting a catalytic crosslinking agent and a tackifier onto the main chain segment of the thermoplastic elastomer to obtain a precursor 1;

[0094] Grafting a polar coupling agent onto precursor 1 to obtain precursor 2;

[0095] Grafting a cross-linking agent onto the hydrolyzable functional group of the polar coupling agent of the precursor 2 to obtain an intermediate;

[0096] The intermediate is extruded to obtain a direct injection modifier.

[0097] In some preferred embodiments, the above method is specifically as follows:

[0098] S1. Precursor preparation: a thermoplastic elastomer is mixed with a catalytic crosslinking agent and a tackifier, stirred evenly, and heated at 120-180° C. to form a co-melting reaction to obtain a precursor 1;

[0099] S2, polar coupling agent grafting: the temperature is lowered to 100°C, and high-speed stirring is continued. The -CHO, -COOH and other groups of the catalytic cross-linking agent and the tackifier in the precursor are used to form a charge-acting intermolecular force with the polar group at one end of the polar coupling agent chain segment, and the polar coupling agent is grafted to obtain precursor 2;

[0100] S3, grafting of crosslinking agent: continuously stirring at high speed, utilizing the intermolecular force and charge effect formed on the hydrolyzable functional groups of thiazole and disulfide carbamate on the crosslinking agent and the polar coupling agent to graft the crosslinking agent to obtain an intermediate;

[0101] S4, extrusion molding: the intermediate is extruded through a screw extruder in an extrusion device, cooled by water at room temperature, and cut into shape.

[0102] In some preferred embodiments, the extrusion temperature of the screw extruder is 110-165°C.

[0103] This specific embodiment also provides a method for using a direct-injection modifier capable of adjusting the degree of crosslinking, comprising the following steps:

[0104] Mixing the direct-injection modifier with the heated aggregate;

[0105] Adding asphalt and mixing to obtain asphalt mixture;

[0106] Spread and roll the asphalt mixture.

[0107] In some preferred embodiments, the above application method is specifically as follows:

[0108] Modifier direct mixing: the modifier is added into the heated aggregate;

[0109] Mixing: The modifier is melted and mixed with asphalt and aggregate in a mixing plant;

[0110] The mixed asphalt mixture is spread and rolled.

[0111] In some preferred embodiments, the method for using the direct injection modifier comprises the following steps:

[0112] P1. Direct mixing of modifier: Add graded aggregates according to the mix ratio requirements, heat to 160-1901℃, stir, and add direct modifier to the heated aggregates according to the specified ratio;

[0113] P2, mixing: After step P1 is mixed for 15 to 60 seconds, add the proportion of heated asphalt, and mix the modifier with asphalt and aggregate in the mixing plant for 40 to 60 seconds after the modifier is melted;

[0114] P3. The asphalt mixture is transported insulated after mixing. After arriving at the site, it is evenly, slowly and continuously discharged and spread. After initial compaction, repeated compaction and final compaction, it can be cooled to room temperature.

[0115] Example 1

[0116] The present embodiment provides a direct injection modifier with adjustable crosslinking degree, which is composed of 30 parts of thermoplastic elastomer and 20 parts of de-crosslinking agent, 10 parts of polar coupling agent, 20 parts of catalytic crosslinking agent and 20 parts of tackifier in which the main chain segment is grafted from outside to inside.

[0117] The cross-linking agent includes zinc dimethyldithiocarbamate and 2-mercaptobenzothiazole in a mass ratio of 1:1;

[0118] The polar coupling agents are KH550 and KH570, with a mass ratio of 1:1;

[0119] The catalytic cross-linking agent includes formaldehyde, glutaraldehyde and trioxymethylene in a mass ratio of 1:1:1.

[0120] The tackifier is composed of rosin resin, terpene resin, petroleum resin and phenolic resin in a mass ratio of 1:1:1:1.

[0121] The thermoplastic elastomers are linear SBS1301 and star-shaped SBS, with a mass ratio of 1:1.

[0122] The present embodiment provides a method for preparing a direct-injection modifier with adjustable crosslinking degree, comprising the following steps:

[0123] S1, preparation of precursor 1, mixing a thermoplastic elastomer with a catalytic crosslinking agent and a tackifier, stirring evenly, heating and melting at 160° C. to obtain precursor 1;

[0124] S2, polar coupling agent grafting, lowering the temperature to 100°C, continuing high-speed stirring, using the -CHO, -COOH and other groups of the catalytic cross-linking agent and tackifier in precursor 1 and the polar group at one end of the polar coupling agent chain segment to form intermolecular forces, grafting the polar coupling agent, and obtaining precursor 2;

[0125] S3, grafting the cross-linking agent, continuously stirring at a high speed, utilizing the charge effect formed on the hydrolyzable functional groups of the thiazoles and disulfide carbamates on the cross-linking agent and the polar coupling agent to graft the cross-linking agent to obtain an intermediate;

[0126] S4, extrusion molding, the intermediate is extruded through a screw extruder in an extrusion device, cooled by water at room temperature, and cut into shape.

[0127] The extrusion temperature of the screw extruder was 120°C.

[0128] A method for applying a direct-injection modifier capable of adjusting the degree of crosslinking comprises the following steps:

[0129] P1. Direct mixing of modifier: Add graded aggregates according to the PAC-13 mix ratio requirements, heat to 185°C, stir, and add the direct-injection modifier into the heated aggregates;

[0130] P2, mixing: after step P1 is mixed for 60 seconds, PG76-22 asphalt is added according to the mass ratio of direct-injection modifier: asphalt: aggregate = 0.4:4.6:95. After the modifier is melted, it is mixed with asphalt and aggregate in the mixing plant for 60 seconds to obtain asphalt mixture;

[0131] P3. The mixed asphalt mixture is transported insulated for 30 minutes. After arriving at the site, it is evenly, slowly and continuously discharged and spread. After initial compaction, repeated compaction and final compaction, it can be cooled to room temperature.

[0132] Preparation of modified asphalt: at 185° C., the direct injection modifier and PG76-22 asphalt were uniformly mixed in a mass ratio of modifier: asphalt = 92:8 to obtain modified asphalt.

[0133] The properties of the modified asphalt and asphalt mixture prepared in this example are as follows:

[0134] Table 2 Performance test of modified asphalt and modified asphalt mixture

[0135] Test items unit Example 1 <![CDATA[Modified asphalt viscosity, C t,d > Pa·s 200000 <![CDATA[Modified asphalt viscosity and toughness, T0]]> N·m 38.3 <![CDATA[Modified asphalt microscopic adhesion work, W a > / 14.4 <![CDATA[Modified asphalt-aggregate adhesion, t0]]> N·m 31.2 Asphalt mixture scattering, △S % 0.8 Asphalt mixture scattering due to water immersion, △S' % 1.2

[0136] Example 2

[0137] The present embodiment provides a direct-injection modifier with adjustable crosslinking degree, which is composed of 40 parts of thermoplastic elastomer and 10 parts of de-crosslinking agent, 10 parts of polar coupling agent, 20 parts of catalytic crosslinking agent and 20 parts of tackifier, whose main chain segments are grafted from outside to inside.

[0138] The cross-linking agent includes zinc dimethyldithiocarbamate and 2-mercaptobenzothiazole in a mass ratio of 1:1;

[0139] The polar coupling agent is KH550;

[0140] The catalytic cross-linking agent includes formaldehyde and glutaraldehyde in a mass ratio of 1:1.

[0141] The tackifier is composed of rosin resin and terpene resin in a mass ratio of 1:1.

[0142] Thermoplastic elastomer is linear SBS1301.

[0143] The present embodiment provides a method for preparing a direct-injection modifier with adjustable crosslinking degree, comprising the following steps:

[0144] S1, precursor preparation, mixing a thermoplastic elastomer with a catalytic crosslinking agent and a tackifier, stirring evenly, heating and melting at 160° C. to obtain a precursor 1;

[0145] S2, polar coupling agent grafting, lowering the temperature to 100°C, continuing high-speed stirring, using the -CHO, -COOH and other groups of the catalytic cross-linking agent and tackifier in precursor 1 and the polar group at one end of the polar coupling agent chain segment to form intermolecular forces, grafting the polar coupling agent, and obtaining precursor 2;

[0146] S3, grafting the cross-linking agent, continuously stirring at a high speed, utilizing the charge effect formed on the hydrolyzable functional groups of the thiazoles and disulfide carbamates on the cross-linking agent and the polar coupling agent to graft the cross-linking agent to obtain an intermediate;

[0147] S4, extrusion molding, the intermediate is extruded in a screw extruder, cooled by water at room temperature, and cut into shape.

[0148] The extrusion temperature of the screw extruder was 120°C.

[0149] A method for applying a direct-injection modifier capable of adjusting the degree of crosslinking comprises the following steps:

[0150] P1. Direct mixing of modifier: Add graded aggregates according to the PAC-13 mix ratio requirements, heat to 185°C, stir, and add the direct-injection modifier into the heated aggregates;

[0151] P2, mixing: After step P1 is mixed for 60 seconds, add ID asphalt in a mass ratio of modifier: asphalt: aggregate = 0.4:4.6:95. After the modifier is melted, mix it with asphalt and aggregate in the mixing plant for 60 seconds;

[0152] P3. The mixed asphalt mixture is transported insulated for 30 minutes. After arriving at the site, it is evenly, slowly and continuously discharged and spread. After initial compaction, repeated compaction and final compaction, it can be cooled to room temperature.

[0153] Preparation of modified asphalt: at 185° C., the direct injection modifier and ID asphalt were uniformly mixed in a mass ratio of modifier: asphalt = 92:8 to obtain modified asphalt.

[0154] The properties of the modified asphalt and asphalt mixture prepared in this embodiment are as follows:

[0155] Table 3 Performance test of modified asphalt and modified asphalt mixture

[0156] Test items unit Example 2 <![CDATA[Modified asphalt viscosity, C t,d > Pa·s 230000 <![CDATA[Modified asphalt viscosity and toughness, T0]]> N·m 36.3 <![CDATA[Modified asphalt microscopic adhesion work, W a > / 15.4 <![CDATA[Modified asphalt-aggregate adhesion, t0]]> N·m 30.2 Asphalt mixture scattering, △S % 0.7 Asphalt mixture scattering due to water immersion, △S' % 1.1

[0157] This embodiment provides a modified asphalt in a moderately cross-linked state.

[0158] Example 3

[0159] The present embodiment provides a direct-injection modifier with adjustable crosslinking degree, which is for PG76 asphalt, which is heavily crosslinked and has a prolonged mixing and transportation time. It is necessary to adjust the ratio of polar coupling agent and crosslinking promoter, adjust the reaction process, and then adjust the time of crosslinking removal and crosslinking promotion according to the on-site mixing and transportation time. Therefore, the present embodiment provides a direct-injection modifier with adjustable crosslinking degree, which is calculated by weight and consists of 30 parts of thermoplastic elastomer and 20 parts of crosslinking agent, 20 parts of polar coupling agent, 15 parts of catalytic crosslinking promoter and 15 parts of tackifier, which are grafted from outside to inside on the main chain segment.

[0160] The cross-linking agent includes zinc dimethyldithiocarbamate and 2-mercaptobenzothiazole in a mass ratio of 1:1;

[0161] The polar coupling agent is KH550;

[0162] The catalytic cross-linking agent includes formaldehyde and glutaraldehyde in a mass ratio of 1:1.

[0163] The tackifier is composed of rosin resin and terpene resin in a mass ratio of 1:1.

[0164] Thermoplastic elastomer is linear SBS1301.

[0165] The present embodiment provides a method for preparing a direct-injection modifier with adjustable crosslinking degree, comprising the following steps:

[0166] S1, precursor preparation, mixing a thermoplastic elastomer with a catalytic crosslinking agent and a tackifier, stirring evenly, heating and melting at 160° C. to obtain a precursor 1;

[0167] S2, polar coupling agent grafting, lowering the temperature to 100°C, continuing high-speed stirring, using the -CHO, -COOH and other groups of the catalytic cross-linking agent and tackifier in precursor 1 and the polar group at one end of the polar coupling agent chain segment to form intermolecular forces, grafting the polar coupling agent, and obtaining precursor 2;

[0168] S3, grafting the cross-linking agent, continuously stirring at a high speed, utilizing the charge effect formed on the hydrolyzable functional groups of the thiazoles and disulfide carbamates on the cross-linking agent and the polar coupling agent to graft the cross-linking agent to obtain an intermediate;

[0169] S4, extrusion molding, the intermediate is extruded in a screw extruder, cooled by water at room temperature, and cut into shape.

[0170] The extrusion temperature of the screw extruder was 120°C.

[0171] A method for applying a direct-injection modifier capable of adjusting the degree of crosslinking comprises the following steps:

[0172] P1. Direct mixing of modifier: Add graded aggregates according to the PAC-13 mix ratio requirements, heat to 185°C, stir, and add the direct-injection modifier into the heated aggregates;

[0173] P2, mixing: After step P1 is mixed for 60 seconds, add ID asphalt according to the mass ratio of modifier: asphalt: aggregate = 0.4:4.6:95. After the modifier is melted, mix it with asphalt and aggregate in the mixing plant for 60 seconds;

[0174] P3. The mixed asphalt mixture is transported insulated for 30 minutes. After arriving at the site, it is evenly, slowly and continuously discharged and spread. After initial compaction, repeated compaction and final compaction, it can be cooled to room temperature.

[0175] Preparation of modified asphalt: at 185° C., the direct injection modifier and ID asphalt were uniformly mixed in a mass ratio of modifier: asphalt = 92:8 to obtain modified asphalt.

[0176] The properties of the modified asphalt and asphalt mixture prepared in this embodiment are as follows:

[0177] Table 4 Performance test of modified asphalt and modified asphalt mixture

[0178] Test items unit Example 3 <![CDATA[Modified asphalt viscosity, C t,d > Pa·s 240000 <![CDATA[Modified asphalt viscosity and toughness, T0]]> N·m 38.7 <![CDATA[Modified asphalt microscopic adhesion work, W a > / 14.8 <![CDATA[Modified asphalt-aggregate adhesion, t0]]> N·m 31.6 Asphalt mixture scattering, △S % 0.7 Asphalt mixture scattering due to water immersion, △S' % 1.2

[0179] Comparative Example 1

[0180] The present embodiment provides a direct-injection modifier with adjustable crosslinking degree, which comprises, by weight, 30 parts of thermoplastic elastomer, 20 parts of crosslinking agent, 10 parts of polar coupling agent, 20 parts of catalytic crosslinking agent and 20 parts of tackifier.

[0181] The cross-linking agent includes zinc dimethyldithiocarbamate and 2-mercaptobenzothiazole in a mass ratio of 1:1;

[0182] The polar coupling agents are KH550 and KH570, with a mass ratio of 1:1;

[0183] The catalytic cross-linking agent includes formaldehyde, glutaraldehyde and trioxymethylene in a mass ratio of 1:1:1.

[0184] The tackifier is composed of rosin resin, terpene resin, petroleum resin and phenolic resin in a mass ratio of 1:1:1:1.

[0185] The thermoplastic elastomers are linear SBS1301 and star-shaped SBS, with a mass ratio of 1:1.

[0186] The present embodiment provides a method for preparing a direct-injection modifier with adjustable crosslinking degree, comprising the following steps:

[0187] S1, melting a thermoplastic elastomer, a crosslinking agent, a polar coupling agent, a catalytic crosslinking agent and a tackifier at 160° C. to obtain an intermediate;

[0188] S2. Extrude the intermediate in a screw extruder, cool it with normal temperature water, and cut it into shape.

[0189] The extrusion temperature of the screw extruder was 120°C.

[0190] A method for applying a direct-injection modifier capable of adjusting the degree of crosslinking comprises the following steps:

[0191] P1. Direct mixing of modifier: Add graded aggregates according to the PAC-13 mix ratio requirements, heat to 185°C, stir, and add the direct-injection modifier into the heated aggregates;

[0192] P2, mixing: After step P1 is mixed for 60 seconds, add PG76-22 asphalt in a mass ratio of modifier: asphalt: aggregate = 0.4:4.6:95. After the modifier is melted, mix it with asphalt and aggregate in the mixing plant for 60 seconds;

[0193] P3. The mixed asphalt mixture is transported insulated for 30 minutes. After arriving at the site, it is evenly, slowly and continuously discharged and spread. After initial compaction, repeated compaction and final compaction, it can be cooled to room temperature.

[0194] Preparation of modified asphalt: at 185° C., the direct injection modifier and PG76-22 asphalt were uniformly mixed in a mass ratio of modifier: asphalt = 92:8 to obtain modified asphalt.

[0195] The properties of the modified asphalt and asphalt mixture prepared in this embodiment are as follows:

[0196] Table 5 Performance test of modified asphalt and modified asphalt mixture

[0197] Test items unit Example 1 Comparative Example 1 <![CDATA[Modified asphalt viscosity, C t,d > Pa·s 200000 300000 <![CDATA[Modified asphalt viscosity and toughness, T0]]> N·m 38.3 24.6 <![CDATA[Modified asphalt microscopic adhesion work, W a > / 14.4 9.3 <![CDATA[Modified asphalt-aggregate adhesion, t0]]> N·m 31.2 5.8 Asphalt mixture scattering, △S % 0.8 5.7 Asphalt mixture scattering due to water immersion, △S' % 1.2 13.0

[0198] According to the comparison between the above data and Example 1, in this embodiment, PG76 asphalt is used, which is highly cross-linked, and the direct-injection modifier contains a large amount of thermoplastic elastomer molecules. After melting, the cross-linking agent and the thickener act simultaneously to improve the viscosity of the system; it has a certain degree of viscosity and toughness, but because the degree of cross-linking is too high, the active groups in the thickener cannot react with the aggregate, resulting in poor adhesion, which in turn causes the mixture to have a low scattering value and obvious hanging particles, affecting the durability of the pavement structure.

[0199] Comparative Example 2

[0200] The present embodiment provides a direct injection modifier with adjustable crosslinking degree, which is composed of 30 parts of thermoplastic elastomer and 20 parts of de-crosslinking agent, 10 parts of polar coupling agent, 20 parts of catalytic crosslinking agent and 20 parts of tackifier in which the main chain segment is grafted from outside to inside.

[0201] The cross-linking agent includes zinc dimethyldithiocarbamate and 2-mercaptobenzothiazole in a mass ratio of 1:1;

[0202] The polar coupling agents are KH550 and KH570, with a mass ratio of 1:1;

[0203] The catalytic cross-linking agent includes formaldehyde, glutaraldehyde and trioxymethylene in a mass ratio of 1:1:1.

[0204] The tackifier is composed of rosin resin, terpene resin, petroleum resin and phenolic resin in a mass ratio of 1:1:1:1.

[0205] The thermoplastic elastomers are linear SBS1301 and star-shaped SBS, with a mass ratio of 1:1.

[0206] The present embodiment provides a method for preparing a direct-injection modifier with adjustable crosslinking degree, comprising the following steps:

[0207] S1, precursor preparation, mixing a thermoplastic elastomer with a crosslinking agent and a tackifier, stirring evenly, heating and melting at 160° C. to obtain a precursor 1;

[0208] S2, polar coupling agent grafting, lowering the temperature to 100°C, continuing high-speed stirring, utilizing the charge effect formed by the crosslinking agent, tackifier and polar groups at one end of the polar coupling agent chain segment in precursor 1 to graft the polar coupling agent to obtain precursor 2;

[0209] S3, grafting the catalytic cross-linking agent, continuously stirring at a high speed, utilizing the intermolecular force formed on the hydrolyzable functional groups of the catalytic cross-linking agent and the polar coupling agent to graft the catalytic cross-linking agent to obtain an intermediate;

[0210] S4, extrusion molding, the intermediate is extruded in a screw extruder, cooled by water at room temperature, and cut into shape.

[0211] The extrusion temperature of the screw extruder was 120°C.

[0212] A method for applying a direct-injection modifier capable of adjusting the degree of crosslinking comprises the following steps:

[0213] P1. Direct mixing of modifier: Add graded aggregates according to the PAC-13 mix ratio requirements, heat to 185°C, stir, and add the direct-injection modifier into the heated aggregates;

[0214] P2, mixing: After step P1 is mixed for 60 seconds, add PG76-22 asphalt in a mass ratio of modifier: asphalt: aggregate = 0.4:4.6:95. After the modifier is melted, mix it with asphalt and aggregate in the mixing plant for 60 seconds;

[0215] P3. The mixed asphalt mixture is transported insulated for 30 minutes. After arriving at the site, it is evenly, slowly and continuously discharged and spread. After initial compaction, repeated compaction and final compaction, it can be cooled to room temperature.

[0216] Preparation of modified asphalt: at 185° C., the direct injection modifier and PG76-22 asphalt were uniformly mixed in a mass ratio of modifier: asphalt = 92:8 to obtain modified asphalt.

[0217] The properties of the modified asphalt and asphalt mixture prepared in this embodiment are as follows:

[0218] Table 6 Performance test of modified asphalt and modified asphalt mixture

[0219] Test items unit Example 1 Comparative Example 2 <![CDATA[Modified asphalt viscosity, C t,d > Pa·s 200000 500000 <![CDATA[Modified asphalt viscosity and toughness, T0]]> N·m 38.3 12.2 <![CDATA[Modified asphalt microscopic adhesion work, W a > / 14.4 3.5 <![CDATA[Modified asphalt-aggregate adhesion, t0]]> N·m 31.2 7.8 Asphalt mixture scattering, △S % 0.8 15.7 Asphalt mixture scattering due to water immersion, △S' % 1.2 23.7

[0220] Compared with Example 1, when the catalytic cross-linking agent preferentially dissociates under the action of hot aggregate and asphalt, it can form an adsorption effect with the active components in the asphalt, replace H in the asphalt and undergo a condensation reaction, so that the molecular weight of the asphalt increases and presents a continuous streamline distribution, thereby enhancing the degree of cross-linking. The viscosity of the system increases, and it is not conducive to the action of the tackifier on the aggregate surface, and the viscosity and toughness of the asphalt and its adhesion to the aggregate are poor.

[0221] Comparative Example 3

[0222] The present embodiment provides a direct injection modifier with adjustable crosslinking degree, which is composed of 30 parts of thermoplastic elastomer, 10 parts of polar coupling agent, 20 parts of catalytic crosslinking agent and 20 parts of tackifier in which the main chain segment is grafted from outside to inside.

[0223] Among them, the polar coupling agents are KH550 and KH570, and the mass ratio is 1:1.

[0224] The catalytic cross-linking agent includes formaldehyde, glutaraldehyde and trioxymethylene in a mass ratio of 1:1:1.

[0225] The tackifier is composed of rosin resin, terpene resin, petroleum resin and phenolic resin in a mass ratio of 1:1:1:1.

[0226] The thermoplastic elastomers are linear SBS1301 and star-shaped SBS, with a mass ratio of 1:1.

[0227] The present embodiment provides a method for preparing a direct-injection modifier with adjustable crosslinking degree, comprising the following steps:

[0228] S1, precursor preparation, mixing a thermoplastic elastomer with a catalytic crosslinking agent and a tackifier, stirring evenly, heating and melting at 160° C. to obtain a precursor 1;

[0229] S2, polar coupling agent grafting, lowering the temperature to 100°C, continuing high-speed stirring, using the -CHO, -COOH and other groups of the catalytic cross-linking agent and tackifier in the precursor to form intermolecular forces with the polar group at one end of the polar coupling agent chain segment, grafting the polar coupling agent to obtain precursor 2;

[0230] S3, extrusion molding, extruding the precursor 2 in a screw extruder, cooling with room temperature water, and cutting into shape.

[0231] The extrusion temperature of the screw extruder was 120°C.

[0232] A method for applying a direct-injection modifier capable of adjusting the degree of crosslinking comprises the following steps:

[0233] P1. Direct mixing of modifier: Add graded aggregates according to the PAC-13 mix ratio requirements, heat to 185°C, stir, and add the direct-injection modifier into the heated aggregates;

[0234] P2, mixing: After step P1 is mixed for 60 seconds, add PG76-22 asphalt in proportion according to the mass ratio of modifier: asphalt: aggregate = 0.4:4.6:95. After the modifier is melted, mix it with asphalt and aggregate in the mixing plant for 60 seconds;

[0235] P3. The mixed asphalt mixture is transported insulated for 30 minutes. After arriving at the site, it is evenly, slowly and continuously discharged and spread. After initial compaction, repeated compaction and final compaction, it can be cooled to room temperature.

[0236] Preparation of modified asphalt: at 185° C., the direct injection modifier and PG76-22 asphalt were uniformly mixed in a mass ratio of modifier: asphalt = 92:8 to obtain modified asphalt.

[0237] The properties of the modified asphalt and asphalt mixture prepared in this embodiment are as follows:

[0238] Table 7 Performance test of modified asphalt and modified asphalt mixture

[0239] Test items unit Example 1 Comparative Example 3 <![CDATA[Modified asphalt viscosity, C t,d > Pa·s 200000 530000 <![CDATA[Modified asphalt viscosity and toughness, T0]]> N·m 38.3 14.2 <![CDATA[Modified asphalt microscopic adhesion work, W a > / 14.4 3.8 <![CDATA[Modified asphalt-aggregate adhesion, t0]]> N·m 31.2 6.8 Asphalt mixture scattering, △S % 0.8 12.7 Asphalt mixture scattering due to water immersion, △S' % 1.2 20.5

[0240] Compared with Example 1, there is no de-crosslinking agent, the system viscosity is relatively large, and it is not conducive for the tackifier to enter the aggregate surface, and the adhesion is poor.

[0241] Comparative Example 4

[0242] The present embodiment provides a direct injection modifier with adjustable crosslinking degree, which is composed of 30 parts of thermoplastic elastomer, 20 parts of de-crosslinking agent, 10 parts of polar coupling agent and 20 parts of tackifier in which the main chain segment is grafted from outside to inside, calculated by weight.

[0243] The cross-linking agent includes zinc dimethyldithiocarbamate and 2-thiolbenzothiazole in a mass ratio of 1:1.

[0244] The polar coupling agents are KH550 and KH570, with a mass ratio of 1:1.

[0245] The tackifier is composed of rosin resin, terpene resin, petroleum resin and phenolic resin in a mass ratio of 1:1:1:1.

[0246] The thermoplastic elastomers are linear SBS1301 and star-shaped SBS, with a mass ratio of 1:1.

[0247] The present embodiment provides a method for preparing a direct-injection modifier with adjustable crosslinking degree, comprising the following steps:

[0248] S1, precursor preparation, mixing a thermoplastic elastomer and a tackifier, stirring evenly, heating and melting at 160° C. to obtain a precursor 1;

[0249] S2, polar coupling agent grafting, lowering the temperature to 100°C, continuing high-speed stirring, utilizing the group of the tackifier in precursor 1 and the polar group at one end of the polar coupling agent chain segment to form an intermolecular force, grafting the polar coupling agent, and obtaining precursor 2;

[0250] S3, grafting the cross-linking agent, continuously stirring at a high speed, utilizing the charge effect formed on the hydrolyzable functional groups of the thiazoles and disulfide carbamates on the cross-linking agent and the polar coupling agent to graft the cross-linking agent to obtain an intermediate;

[0251] S4, extrusion molding, the intermediate is extruded in a screw extruder, cooled by water at room temperature, and cut into shape.

[0252] The extrusion temperature of the screw extruder was 120°C.

[0253] A method for applying a direct-injection modifier capable of adjusting the degree of crosslinking comprises the following steps:

[0254] P1. Direct mixing of modifier: Add graded aggregates according to the PAC-13 mix ratio requirements, heat to 185°C, stir, and add the direct-injection modifier into the heated aggregates;

[0255] P2, mixing: After step P1 is mixed for 60 seconds, add PG76-22 asphalt in proportion according to the mass ratio of modifier: asphalt: aggregate = 0.4:4.6:95. After the modifier is melted, mix it with asphalt and aggregate in the mixing plant for 60 seconds;

[0256] P3. The mixed asphalt mixture is transported insulated for 30 minutes. After arriving at the site, it is evenly, slowly and continuously discharged and spread. After initial compaction, repeated compaction and final compaction, it can be cooled to room temperature.

[0257] Preparation of modified asphalt: at 185° C., the direct injection modifier and PG76-22 asphalt were uniformly mixed in a mass ratio of modifier: asphalt = 92:8 to obtain modified asphalt.

[0258] The properties of the modified asphalt and asphalt mixture prepared in this embodiment are as follows:

[0259] Table 8 Performance test of modified asphalt and modified asphalt mixture

[0260] Test items unit Example 1 Comparative Example 3 <![CDATA[Modified asphalt viscosity, C t,d > Pa·s 200000 280000 <![CDATA[Modified asphalt viscosity and toughness, T0]]> N·m 38.3 17.8 <![CDATA[Modified asphalt microscopic adhesion work, W a > / 14.4 3.5 <![CDATA[Modified asphalt-aggregate adhesion, t0]]> N·m 31.2 11.8 Asphalt mixture scattering, △S % 0.8 12.7 Asphalt mixture scattering due to water immersion, △S' % 1.2 20.5

[0261] Compared with Example 1, when there is no catalytic crosslinking agent, the SBS molecules in the modifier and asphalt are all in a non-crosslinked state, the system viscosity is moderate, and only the active groups in the tackifier promote the crosslinking of a small amount of asphalt and modifier molecules. The toughness and adhesion are low.

[0262] Comparative Example 5

[0263] The present embodiment provides a direct injection modifier with adjustable crosslinking degree, which is composed of 30 parts of thermoplastic elastomer, 20 parts of de-crosslinking agent, 10 parts of polar coupling agent and 20 parts of catalytic crosslinking agent for grafting the main chain segment from outside to inside.

[0264] The cross-linking agent includes zinc dimethyldithiocarbamate and 2-thiolbenzothiazole in a mass ratio of 1:1.

[0265] The polar coupling agents are KH550 and KH570, with a mass ratio of 1:1.

[0266] The catalytic cross-linking agent includes formaldehyde, glutaraldehyde and trioxymethylene in a mass ratio of 1:1:1.

[0267] The thermoplastic elastomers are linear SBS1301 and star-shaped SBS, with a mass ratio of 1:1.

[0268] The present embodiment provides a method for preparing a direct-injection modifier with adjustable crosslinking degree, comprising the following steps:

[0269] S1, precursor preparation, mixing a thermoplastic elastomer and a catalytic crosslinking agent, stirring evenly, heating and melting at 160° C. to obtain a precursor 1;

[0270] S2, polar coupling agent grafting, lowering the temperature to 100°C, continuing high-speed stirring, using the group of the catalytic cross-linking agent in precursor 1 and the polar group at one end of the polar coupling agent chain segment to form an intermolecular force, grafting the polar coupling agent, and obtaining precursor 2;

[0271] S3, grafting the cross-linking agent, continuously stirring at a high speed, utilizing the charge effect formed on the hydrolyzable functional groups of the thiazoles and disulfide carbamates on the cross-linking agent and the polar coupling agent to graft the cross-linking agent to obtain an intermediate;

[0272] S4, extrusion molding, the intermediate is extruded in a screw extruder, cooled by water at room temperature, and cut into shape.

[0273] The extrusion temperature of the screw extruder was 120°C.

[0274] A method for applying a direct-injection modifier capable of adjusting the degree of crosslinking comprises the following steps:

[0275] P1. Direct mixing of modifier: Add graded aggregates according to the PAC-13 mix ratio requirements, heat to 185°C, stir, and add the direct-injection modifier into the heated aggregates;

[0276] P2, mixing: After step P1 is mixed for 60 seconds, add PG76-22 asphalt in proportion according to the mass ratio of modifier: asphalt: aggregate = 0.4:4.6:95. After the modifier is melted, mix it with asphalt and aggregate in the mixing plant for 60 seconds;

[0277] P3. The mixed asphalt mixture is transported insulated for 30 minutes. After arriving at the site, it is evenly, slowly and continuously discharged and spread. After initial compaction, repeated compaction and final compaction, it can be cooled to room temperature.

[0278] Preparation of modified asphalt: at 185° C., the direct injection modifier and PG76-22 asphalt were uniformly mixed in a mass ratio of modifier: asphalt = 92:8 to obtain modified asphalt.

[0279] The properties of the modified asphalt and asphalt mixture prepared in this embodiment are as follows:

[0280] Table 9 Performance test of modified asphalt and modified asphalt mixture

[0281] Test items unit Example 1 Comparative Example 3 <![CDATA[Modified asphalt viscosity, C t,d > Pa·s 200000 290000 <![CDATA[Modified asphalt viscosity and toughness, T0]]> N·m 38.3 30.2 <![CDATA[Modified asphalt microscopic adhesion work, W a > / 14.4 13.5 <![CDATA[Modified asphalt-aggregate adhesion, t0]]> N·m 31.2 15.4 Asphalt mixture scattering, △S % 0.8 5.6 Asphalt mixture scattering due to water immersion, △S' % 1.2 14.7

[0282] Compared with Example 1, it can be seen that when there is no thickener, the SBS molecules in the modifier and asphalt can re-form a cross-linked state, the system viscosity is moderate, and the modified asphalt has high viscosity and toughness, but it cannot improve the bonding performance between asphalt and aggregate, and the adhesion is low, resulting in a low scattering value.

[0283] It should be noted that, in this specific implementation, the direct injection modifier is mixed with asphalt and aggregate and then evaluated according to the following method:

[0284] (1) Modified asphalt viscosity:

[0285] Refer to JTG E20-2011 "Highway Engineering Asphalt and Asphalt Mixture Test Procedure" T0621-1993, asphalt standard viscosity test (road asphalt standard viscometer method) test, calculated as C t,d , unit: s.

[0286] (2) Viscosity and toughness of modified asphalt:

[0287] Refer to T0624-2011 in JTG E20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering", asphalt viscosity and toughness test, denoted as T0, unit is N·m.

[0288] (3) Microscopic adhesion work of modified asphalt:

[0289] The aggregate stone slabs were cut and polished flat using a metallographic polishing machine to have a smooth surface. The contact angle between asphalt and the surface of the stone slab was measured using a contact angle meter; the adhesion work was calculated: W a =γ a (1+cosθ); where γ a is the surface tension of asphalt, and θ is the contact angle between asphalt and aggregate.

[0290] (4) Modified asphalt-aggregate adhesion:

[0291] Cut aggregates of corresponding sizes according to the mold, dry the aggregates, pour hot asphalt until the surface of the aggregate is flush, put the mold into a 150°C oven for 20 minutes, cool it at room temperature for 1.5 hours, demould it, and then put the sample into a 25°C water bath for 1.5 hours. Use a tensile testing machine to complete the tensile loading test within 20 seconds at a rate of 500mm / min, and get a curve with load (N) as the horizontal axis and displacement (mm) as the vertical axis.

[0292] Modified asphalt-aggregate adhesion (t0) is the area enclosed by the load-displacement curve measured in the test and the abscissa.

[0293] (5) Scattering of asphalt mixture:

[0294] Refer to T0733-2011 in JTG E20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering", Kentburgh Scattering Test for Asphalt Mixture, recorded as △S.

[0295] (6) Asphalt mixture scattering in water:

[0296] Referring to T0733-2011 in JTG E20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering", the Kentburgh Scattering Test for Asphalt Mixtures, the specimens are cured in a constant temperature water tank for 48 hours, recorded as △S'.

[0297] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been presented as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A direct-injection modifier capable of adjusting the degree of crosslinking, characterized in that: The direct injection modifier is based on a thermoplastic elastomer, and a polymer of a crosslinking agent, a polar coupling agent, a catalytic crosslinking agent and a tackifier is grafted from outside to inside on the main chain segment of the thermoplastic elastomer; Calculated by weight, the components for preparing the direct injection modifier include: 30-40 parts of thermoplastic elastomer, 10-20 parts of crosslinking agent, 5-10 parts of polar coupling agent, 10-20 parts of catalytic crosslinking agent and 10-20 parts of tackifier; In the process of heating and mixing the direct injection modifier and asphalt, the grafting of the main chain segment is released step by step from the outside to the inside.

2. A direct-injection modifier with adjustable crosslinking degree according to claim 1, characterized in that: After being released, the cross-linking agent can form a complex centered on zinc ions.

3. A direct-injection modifier with adjustable crosslinking degree according to claim 2, characterized in that: The cross-linking agent includes thiazole and zinc disulfide carbamate; Among them, the structural formula of thiazole is as follows: Wherein, n is 1 or 2, and R is one of hydrogen, zinc or a benzo group.

4. A direct-injection modifier with adjustable crosslinking degree according to claim 2, characterized in that: The structural formula of the zinc disulfide carbamate is as follows: Wherein, R1 is any one of methyl, ethyl, butyl, phenyl or benyl; R2 is any one of methyl, ethyl, butyl, phenyl or benzyl.

5. A direct-injection modifier with adjustable crosslinking degree according to claim 1, characterized in that: One end of the polar coupling agent is a polar group, connecting the catalytic cross-linking agent and the tackifier; The other end is a hydrolyzable functional group, which connects to the cross-linking agent by charge action.

6. A direct-injection modifier with adjustable crosslinking degree according to claim 5, characterized in that: The molecular structure of the catalytic cross-linking agent contains R-CHO, wherein R is an alkyl group.

7. A direct-injection modifier with adjustable crosslinking degree according to claim 5, characterized in that: The tackifier contains one or more of -NH3, -COOH or -CONH.

8. A direct-injection modifier with adjustable crosslinking degree according to claim 1, characterized in that: The thermoplastic elastomer is one or a combination of linear SBS and star-shaped SBS; The relative molecular mass range is 80000~120000; The block ratio is 8:2 to 6:4; The relative density is 0.92~0.

95.

9. The method for preparing a direct-injection modifier with adjustable crosslinking degree according to any one of claims 1 to 8, characterized in that: The steps include: Grafting a catalytic crosslinking agent and a tackifier onto the main chain segment of the thermoplastic elastomer to obtain a precursor 1; Grafting a polar coupling agent onto precursor 1 to obtain precursor 2; Grafting a cross-linking agent onto the hydrolyzable functional group of the polar coupling agent of the precursor 2 to obtain an intermediate; The intermediate is extruded to obtain a direct injection modifier.

10. The use of a direct-injection modifier with adjustable crosslinking degree according to any one of claims 1 to 8, characterized in that: The steps include: Mixing the direct-injection modifier with the heated aggregate; Adding asphalt and mixing to obtain asphalt mixture; Spread and roll the asphalt mixture.